The paradox of progress: Unraveling the complex impact of e-government and business ease on economic growth in the Arab world - Maiss, Amale El; Taher, Hanadi (International Journal of Management and Sustainability, 2024)
This research examines how the ease of doing business (EDB) and electronic government (EGOV) collectively influence economic growth in Arab countries. By applying a fixed effects model to panel data from 2004 to 2022, the study encompasses multiple Arab nations to ensure comprehensive and reliable outcomes. The analysis reveals that the combined effect of EDB and EGOV (EGOVEDB) negatively impacts economic growth, where a one percentage point increase in EGOVEDB corresponds to a 3.52 percentage point decrease in GDP. Additionally, the human development index (HDI) shows a minor negative correlation with economic growth, while foreign direct investment (FDI) shows a slight positive relationship with GDP, indicating a limited effect. These findings suggest that instead of solely focusing on implementing e-government initiatives, we should place greater emphasis on attracting investments, enhancing e-government processes (including infrastructure and regulatory frameworks), and improving HDI to promote economic growth in the Arab world.